2003
DOI: 10.1016/j.physletb.2003.07.073
|View full text |Cite
|
Sign up to set email alerts
|

Quintessence and the relic density of neutralinos

Abstract: The archetypal model for the recently discovered dark energy component of the universe is based on the existence of a scalar field whose dynamical evolution comes down today to a non-vanishing cosmological constant. In the past -before big-bang nucleosynthesis for that matter -that scalar field could have gone through a period of kination during which the universe has expanded at a much higher pace than what is currently postulated in the standard radiation dominated cosmology. I examine here the consequences … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
273
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(278 citation statements)
references
References 32 publications
4
273
1
Order By: Relevance
“…Although 1−3w is ≈ 0 throughout most of the early universe, there is an important effect that arises when each of the particle species in the cosmic fluid becomes non-relativistic [27]. 7 The choice V (ϕ * ) = 0 does not give a viable late time cosmology in that it cannot account for the recent accelerated expansion of our universe. Coc et al [37] have studied the effects of including a cosmological constant (in either the Jordan or Einstein frames) tuned to the observed value of the cosmological constant density today and find that only the late time dynamics of the scalar field is affected.…”
Section: Scalar Field Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although 1−3w is ≈ 0 throughout most of the early universe, there is an important effect that arises when each of the particle species in the cosmic fluid becomes non-relativistic [27]. 7 The choice V (ϕ * ) = 0 does not give a viable late time cosmology in that it cannot account for the recent accelerated expansion of our universe. Coc et al [37] have studied the effects of including a cosmological constant (in either the Jordan or Einstein frames) tuned to the observed value of the cosmological constant density today and find that only the late time dynamics of the scalar field is affected.…”
Section: Scalar Field Dynamicsmentioning
confidence: 99%
“…If the universe experiences a non-standard expansion law at early times, and in particular during the era of dark matter decoupling, particle freeze-out may be accelerated (or delayed) and the relic abundance enhanced (or suppressed) [4][5][6][7][8][9][10][11][12] (see also [13]). …”
Section: Introductionmentioning
confidence: 99%
“…A kination is a period in which the kinetic energy of a scalar field ρ φ ≃φ 2 /2 dominates over the potential energy density V (φ) and the radiation energy density ρ rad . A kination phase is appeared in quintessence models based on tracking solutions for the scalar field [7]. The overall energy density decreases as ρ tot ≃φ 2 /2 ∼ R −6 .…”
Section: Relic Abundance Of Wimps In Quintessencementioning
confidence: 99%
“…The reason for that might be the additional contributions to the total energy density from quintessence model [7], anisotropic expansion [8], a modification of general relativity [8,9] and etc. In paper by Salati [7], it was shown that the relic density of Dark…”
Section: Introductionmentioning
confidence: 99%
“…Although this model does not possess a tracker-type solution [11,39] in the allowed range of its parameters, it can produce a viable present-day cosmology in conjunction with the domination of an early KD era, for a reasonable region of initial conditions [40,41,42,43]. We then investigate the impact of KD on the thermal production of e-WIMPs, solving the relevant equations both numerically and semianalytically.…”
Section: Introductionmentioning
confidence: 99%